Mainstreaming Pancasila-Based Deradicalization in Indonesia - Abdul Rahman (CV. Ulil Albab Corp, 2024)
Rejection of Pancasila can be used as the main measure of radicalism. This is due to the benchmark that if radical circles can accept Pancasila, then state development and nationalist values ​​will be accepted. Therefore, acceptance of Pancasila is the main condition for efforts to deradicalize religion. The emergence of radicalism arises from a lack of understanding regarding national ideology. If an understanding of Pancasila is developed, then radicalism logically shifts to moderation. This article aims to elaborate on the role of Pancasila in overcoming radical actions in the name of religion in Indonesia. The method used in writing this article is through literature review. The author explores various sources related to the study topic. The sources in question are books, journals and online media. The results of the study show that in the current era of globalization, Pancasila as an open ideology is confronted with various world ideologies, including transnational Islamic ideology which sometimes carries out violent actions to achieve its goals. However, the government must not be defeated by this ideology, and must continue to maintain Pancasila as the ideology of the Indonesian State, because Pancasila is the result of tracing various wisdom that has lived and developed in Indonesia since the archipelago era in the past.